Personalized Therapy for Generalized Lymphatic Anomaly/Gorham-Stout Disease With a Combination of Sunitinib and Taxol. Issue 8 (November 2015) - Rössler, Jochen; Saueressig, Ulrich; Kayser, Gian; von Winterfeld, Moritz; Klement, Gianoula L.
Abstract : The recently revised ISSVA classification approved in Melbourne in April 2014 recognizes generalized lymphatic anomaly and lymphatic malformation in Gorham-Stout disease. The 2 entities can overlap in presentation, as both are characterized by destructive lymphatic vessel invasion of the axial skeleton and surrounding soft tissues. At least at present, no standard therapeutic options exist, and due to the rarity of the disease, no clinical trials are available. We present 2 patients, 1 with generalized lymphatic anomaly and 1 with lymphatic malformation in Gorham-Stout disease, with severe exacerbation during puberty. The first child presented in florid pulmonary failure and pleural effusion, the other with severe pain due to bone destruction of the pelvis and inability to walk. Both were treated using individualized protocols. The manuscript describes the rationale for choosing sunitinib in combination with low-dose (metronomic) taxol. Both patients experienced clinical and radiologic response without major toxicities, suggesting that patients with rare conditions may benefit from individualized, molecularly based therapies. Abstract : Supplemental Digital Content is available in the text.